A bibliometric analysis of evolving trends in CEO characteristics and financial performance research - M. Erry Sugiharto; Agung Nur Probohudono; Djoko Suhardjanto; Wahyu Widarjo (Cogent Business & Management, 2024)
In the past decade, there has been considerable scholarly focus on studying the characteristics of Chief Executive Officers (CEOs) and their influence on the financial performance of organizations. Nonetheless, a notable lacuna exists within the academic literature in the form of a comprehensive survey encompassing CEO characteristics and their nexus with financial performance. This study aims to furnish a cutting-edge synopsis of the academic discourse on CEO characteristics and corporate financial performance. To accomplish this, we employed a systematic approach involving the PRISMA protocol, VOSViewer, and R for an in-depth analysis. Our analytical framework relies on an extensive Scopus dataset spanning 2011 to 2023. 843 scholarly publications have been obtained from the aforementioned leading database. Our findings reveal a notable surge in research activity within this domain over the preceding 13 years, culminating in its zenith in 2023. This surge can be primarily ascribed to amplified avenues for scholarly dissemination and concerted scholarly endeavors, particularly in the United States and China. Furthermore, the robust support of academic institutions, coupled with prolific authorship, is seen as a significant catalyst for this burgeoning trend. In summary, this study synthesizes the previously fragmented literature and offers prospective avenues for future scholarly research.
Keywords: 650; CEO characteristics; financial performance; bibliometric analysis; literature review; upper echelons theory